Middle Miocene sediments on the northern part of Gorjanci between Čatež and Kostanjevica (SE Slovenia) - Rižnar, Igor; Miletić, Danica; Verbič, Tomaž; Horvat, Aleksander (Geologija, 2002)
The oldest Neogene marine sedimentary rocks on the northern slopes of Gorjanci are ascribed to Upper Badenian. On the basis of the lithologic characteristics five different lithotypes were recognized and they can be combined into one lithostratigraphic column.. Although the sedimentation has been controlled by the sinsedimentary tectonics we can identify all Badenian global eustatic events (sequences). According to foraminiferal biostratigraphy the lithologic succesion can be into the Upper Badenian Bulimina - Bolivina biozone and Lower Sarmatian zone of the Elphidium reginum biozone. The Bulimina - Bolivina biozone reflects the stratification of water masses suggesting a high-stand deposits that can be correlated to the HS TB 2.4 eustatic cycle and the upper part of the nannoplankton NN5 biozone respectively. The lithologic succesion is assigned to one formation divided into two members: the lower carbonate and the upper clastic one. We propose the name Čatež formation for the described lithologic succession.